Independence of Notary PPAT As Bank Partner - Hendrik Handoyo Lugito; Nynda Fatmawati Octarina (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2021)
Notary as a public official who has the authority to make authentic deeds and other deeds mandated by law, where the authentic deeds in accordance with Article 1868 of the Civil Code are deeds made in the form stipulated by law by or in the presence of public officials authorized to that is at the place where the deed was made, and has perfect evidentiary power before a court, unless otherwise stated. In the Bank's operational activities related to the function of the Bank as a channeling institution for funds to the public, it is very necessary to have an authentic deed as a form of legality recognition of the engagement between the Bank and its debtors, and therefore the role of a notary as a partner is urgently needed. However, in the fact, implementation, the Notary must provide an offer to the Bank so that he can enter into a cooperation agreement with the Bank for the preparation of authentic deeds and other matters. The existence of a cooperation agreement between the Bank and the Notary has resulted in the Notary's independence being questioned because it seems as if the Bank can do anything because he is the employer and the Notary is the recipient of the work. Therefore, this study analyzes the level of independence of a notary when he becomes a partner in a bank by conducting research with the juridical-normative method and using a statutory and conceptual approach. The results obtained from this research are the existence of cooperation with the Bank to make the Notary as part of the Bank so that he is not independent in making authentic deeds including in his daily practice both before the cooperation until the time of cooperation. And on this matter, if it is proven that the Notary is not independent, then the authentic deed he has made will become deeds under the hands of the Notary and is threatened by being sued by parties who feel aggrieved by the authentic deed.